Impact of Pandemic COVID-19 on the Teaching – Learning Process : A Study of Higher Education Teachers - Arora, Amit Kumar; Srinivasan, R. (Prabandhan: Indian Journal of Management, 2020)
The world is battling COVID-19 and economies across the globe have declared a lockdown. Work from home (WFH) has become the norm, especially for service organizations. Following government instructions, even the academic institutions had to shut down temporarily, affecting academic delivery. Thus, they had to find new alternatives to academic delivery, and virtual classes were the way forward. In the present paper, we attempted to study the impact of lockdown on the teaching – learning process. The objective of the study was to assess the adoption rate for virtual classes and to determine the various benefits, challenges, and reasons for non - adoption of virtual classes. The study considered responses from 341 teachers of higher education institutions (HEIs) of Ghaziabad region. The study was divided into two parts. One set of respondents were those who adopted virtual classrooms and another set that did not adopt virtual classrooms. Descriptive statistics and t - test were performed to analyze the data collected through primary sources. Among those who adopted virtual mode, the mean of actual benefits was significantly less than the mean of expected benefits. Network issues, lack of training, and lack of awareness were stated to be the major challenges faced by them. Lack of awareness was stated to be the most important reason by those who did not adopt virtual classrooms followed by lack of interest and doubts regarding the usefulness of virtual classes. Less attendance, lack of personal touch, and lack of interaction due to connectivity issues were found to be the significant drawbacks of virtual classes. The study also suggested the ways to overcome the above challenges, drawbacks, and reasons behind non - adoption of virtual classes.